PELATIHAN PENGOLAHAN LIMBAH PERTANIAN DI DESA NGEPOSARI - Masayu Alya Nuraini; Yessi Jusman; Ahmad Zaki; Wikan Tyassari (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
One potential source of biomass energy to be processed is agricultural waste. Seeing the potential of corn cultivation owned by the people of Ngeposari Village, corn waste processing is considered to have opportunities in economic terms. Corn weevils have been used by residents to make embers without further processing. Household waste and agricultural waste often harm society. Waste that is a leftover or discarded product is always considered unusable. The existing waste accumulates and has a negative effect. Proper processing of waste can open up new business opportunities. Agricultural waste is one biomass energy source with high selling value but has yet to be widely utilized. The service team offers solutions to revive UMKM in Ngeposari Village, Gunung Kidul, and increase community business opportunities through this service program. Several pieces of training were conducted to increase the skills of residents, namely training in making briquettes from corn stalks and training in making organic fertilizer.